Radial heterojunction based on single ZnO-Cu(x)O core-shell nanowire for photodetector applications - Costas, Andreea (Sci Rep, 2019)
ZnO-Cu(x)O core-shell radial heterojunction nanowire arrays were fabricated by a straightforward approach which combine two simple, cost effective and large-scale preparation methods: (i) thermal oxidation in air of a zinc foil for obtaining ZnO nanowire arrays and (ii) radio frequency magnetron sputtering for covering the surface of the ZnO nanowires with a Cu(x)O thin film. The structural, compositional, morphological and optical properties of the high aspect ratio ZnO-Cu(x)O core-shell nanowire arrays were investigated. Individual ZnO-Cu(x)O core-shell nanowires were contacted with Pt electrodes by means of electron beam lithography technique, diode behaviour being demonstrated. Further it was found that these n-p radial heterojunction diodes based on single ZnO-Cu(x)O nanowires exhibit a change in the current under UV light illumination and therefore behaving as photodetectors.